The International Education Market: Some Emerging Trends - Kemp, Neil (International Higher Education, 2016)
This article provides a brief overview of recent trends in international student mobility and implications for higher education institutions as they seek to recruit international students. International student mobility has continued to surge, as reflected in recent data from most major destination countries. However changes are occurring, some large and some subtle, and a selection of these trends are briefly discussed below. The major exception to strong enrolment growth in recruitment has been the UK, where tough immigration regulations have impacted directly on international student numbers.